Norwegian validation of the University Student Engagement Inventory - Løken, Trygve K.; Hanssen, Natallia B.; Olsen, Kathrin; Marôco, João (Frontiers in Psychology, 2026)
This study reports on the validation of the University Student Engagement Inventory (USEI) in a Norwegian context. The USEI conceptualizes student engagement (SE) as a three-factor first-order construct encompassing cognitive, emotional, and behavioral dimensions and as a second-order construct. Psychometric analysis was conducted with a sample of 833 students from Norwegian universities and university colleges, representing both science, technology, engineering, and mathematics (STEM) and non-STEM fields (humanities and social sciences). Psychometric analysis is reported, including distributional properties, sources of evidence related to the internal structure, and external criteria. The paper presents an invariance analysis for area of study and gender. Criterion validity was evaluated with respect to students’ dropout intention, failed university courses, and use of medication to cope with study-related challenges. The USEI demonstrated good factorial construct validity and reliability for both the first- and second-order constructs. Higher levels of SE significantly predicted lower dropout intentions, fewer failed courses, and reduced medication use among Norwegian students. The study demonstrates that the USEI can deliver reliable, valid data on SE in the Norwegian context. It has predictive value for academic variables and is therefore important for policymakers and stakeholders in the education system.